Implementasi Peran Serta Masyarakat dalam Pemberantasan Tindak Pidana Korupsi di Sumatera Barat - Ramadhan Hamzah (Jurnal Ilmiah Penegakan Hukum, 2019)
Public participation is the active role of individuals, community organizations, or NGOs in the prevention and eradication of corruption. Forms of public participation contained in Articles 41 and 42 of Law on Corruption Eradication/PTPK. As a subject matter that will be explored, namely: 1) How does the implementation of public participation in efforts to combat corruption in West Sumatra. 2) What are the obstacles for people to take part in efforts to combat corruption. 3) Are efforts made to overcome the obstacles to participate in efforts to combat corruption. The research method used is the juridical sociological/empirical. Results and discussion of the study show that: 1) The role of the community in this regard NGOs in West Sumatra is high enough effort in eradicating corruption in West Sumatra, it is seen from the various agendas that have been implemented, one of which anti-corruption education among students. 2) Constraints were found to participate in the eradication of corruption is internal and external constraints. 3) The efforts made by NGOs to overcome the internal obstacles are: Engaging the worshiper in discussions and training, open opportunities for students who have graduated to serve in institutions, maximize fundraising. While the effort to overcome external obstacles are: Enterprising discussions with law enforcement agencies, civic groups reported the formation of the government and the owners of capital who intimidate activists to the authorities, forming the Division Fundraising, is eager to press conferences and media discussion and establishment of shelters Monitoring and Advocacy Mafia Law.